The Development of Interactive Flipbook Teaching Supplement Mechanism of Heavy Metal Toxicokinetic Based on Laboratory Research - Intan Kharyna Solekhah; Aditya Marianti (FMIPA UNNES, 2023)
This study aims to describe the characteristics and analyze the feasibility of interactive flipbook teaching supplements on heavy metal toxicokinetic mechanisms based on laboratory research as supporting teaching materials in the learning process. This research was conducted at the Laboratory of the State University of Semarang and SMA N 12 Semarang. The type of research is research and development (RnD). The subjects of this study were material experts and media experts to assess the feasibility of materials and designs of laboratory research-based interactive flipbook teaching supplements, as well as students of class XII MIPA 4 and teachers of biology subjects at SMA N 12 Semarang to see the effectiveness of teaching supplements through response questionnaires response. The results showed that the characteristics of the interactive flipbook teaching supplement were developed to contain the results of the latest laboratory research as a learning resource for students, easy to use and exciting, and could help understand the material. The feasibility of interactive flipbook teaching supplements based on laboratory research is based on assessing material expert validators at 88.86% and media expert validators at 93.75%. Based on the responses of students and teachers, teaching supplements are considered exciting and suitable for use, with percentages of 86.39% and 96.25%, respectively. It shows that the interactive flipbook teaching supplement based on laboratory research produced in this study is considered to meet the characteristics of an interactive teaching supplement containing research and is suitable to be used to support the fulfillment of KD material on the digestive system and excretory system.